Managing private institutions of higher learning.An interview with the Deputy Director General of the Department of higher education management (Private Higher Education) - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)

(untitled)
Private Higher Education in Malaysia is a n important component for nation building and has contributed enormously to the development of the country and its human capital.